MINILAPAROTOMY FAMILY PLANNING, STUDY PROVINCES - Samamé Boggio, Guido (2015)
304 cases before the technique minilaparotomy that were performed in twenty different cities, to perform tubal occlusion and achieve the ultimate female sterilization to control their fertility, elective surgeries mostly and in a smaller number reported in the post partum. Previously, all patients and their partners completed a request, which was evaluated by a committee of the Department of Gynecology and Obstetrics, which saw multiparity, age, coexisting with intercurrent diseases, socio-economic status, etc. In postpartum, the intervention was performed within 24-48 hours of delivery; in non-puerperal it was made after the rule. The incision above the pubis was 3-4 cms. , Somewhat longer than usual, for the convenience of the demonstration of the technique of tubal blockage. In 74% of cases, age ranged from 30 to 39, married the great majority. The average number of births per woman was 6 and 6.7 of pregnancies. The type of anesthesia used was the general; spinal and epidural in fewer cases.